2005
DOI: 10.1007/s00270-004-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Self-Expanding Versus Balloon-Expandable Stents in a Human Ex Vivo Model

Abstract: The objective was to compare the radial strength and expansile precision of self-expanding stents and balloon-expandable stents in a human cadaver bifurcation model. Seven different self-expanding (LUMINEXX, JOSTENT SelfX, JOSTENT SelfX hrf, Sinus-Repo, Sinus SuperFlex, Easy Wallstent, SMART) and four different balloon-expandable stent models (Palmaz, Sinus Stent, SAXX Medium, JOSTENT peripheral), each type 10 stents (total n = 110 stents) were implanted into the common iliac arteries of human cadaver corpses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…The insufficient stent scaffolding also accords with the experimental results of nitinol stents, which had considerably lower radial expansion force than stainless-steel stents (Grenacher et al, 2006). This phenomenon can be partially explained by much lower Young's modulus of nitinol (60 GPa here) than that of stainless steel (about 200 GPa).…”
Section: Article In Presssupporting
confidence: 71%
See 1 more Smart Citation
“…The insufficient stent scaffolding also accords with the experimental results of nitinol stents, which had considerably lower radial expansion force than stainless-steel stents (Grenacher et al, 2006). This phenomenon can be partially explained by much lower Young's modulus of nitinol (60 GPa here) than that of stainless steel (about 200 GPa).…”
Section: Article In Presssupporting
confidence: 71%
“…However, in-stent restenosis of CAS still remains (Clark et al, 2006) and a trial to prove noninferiority of CAS vs. CEA failed recently (Ringleb et al, 2006). The nitinol stent biomechanical properties and stent-vessel interactions are considered as two of major factors of shortand long-term stenting outcomes (Hart et al, 2006), which are studied by experiments (Tanaka et al, 2004;Hanus and Zahora, 2005;Grenacher et al, 2006) or finite element methods (FEM) (Whitcher, 1997;Migliavacca et al, 2004;Brand and Ryvkin, 2005). However, nitinol stent implantation in carotid arteries has not been studied by FEM yet.…”
Section: Introductionmentioning
confidence: 98%
“…In a study with longer follow-up (4 years) but with smaller sample size, all patients showed at least 2 mm of neck dilatation [33]. These results follow a previous description that the self-expandable stent-grafts dilate the aortic neck until the nominal diameter of the stent graft is reached [34]. This initial adaptation has been reported for almost all the self-expandable endograft-treated aortic necks as an adjustment to the devices present and is associated with the percentage of oversizing [31].…”
Section: Biomechanics and Vessel Remodelingsupporting
confidence: 74%
“…Moreover, precision and reproducibility of the achieved expansion was significantly lower in the self-expanding group 47. As the self-expandable stent begins to emerge from the constraint, there is a natural tendency for it to spring forward that results from several stent properties, including bridge design, longitudinal stiffness, and friction.…”
Section: Self-expanding Stents and Aiodmentioning
confidence: 96%